North Korea - US relations : from Kim Jong Il to Kim Jong Un - Pacheco Pardo, Ramon (London ; New York, NY : Routledge/Taylor & Francis Group, 2020)
'How has North Korea sought to normalize diplomatic relations with the US? Explaining the continuities between the Kim Jong-un and Kim Jong-il governments, as well as the discontinuities, especially the decisive move towards brinkmanship under Kim Jong-un culminating in 2017, this book shows how North Korea has constantly learnt from its own experience and the experience of others to evolve and adapt its policy towards the US. This fully revised and expanded second edition draws on interviews and conversations with American, North and South Korean, Chinese and other countries' policy-makers and experts and North Korean official media stories. It has been updated to include discussion of the post-2012 period when Kim Jong-un replaced his father to become the leader of North Korea, and provides detailed analysis of both presidencies, concluding with a study of the two bilateral summits held with President Donald Trump'--
North Korea and the Clinton administration -- Pre-nuclear North Korea and the Bush administration -- Nuclear North Korea and the Bush administration -- Nuclear North Korea under Kim Jong Il and the Obama administration -- Nuclear North Korea under Kim Jong Un and the Obama administration -- Nuclear North Korea and the Trump administration.
Includes bibliographical references (pages 209-250) and index.
Keywords: United States -- Foreign relations -- Korea (North).; Korea (North) -- Foreign relations -- United States; Korea (North) -- Foreign relations